Smart development banks - Eduardo Fernández Arias; Ricardo Hausmann; Ugo Panizza (Inter-American Development Bank (IDB), 2019)
The conventional paradigm about development banks is that these institutions exist to target well-identified market failures. However, market failures are not directly observable and can only be ascertained with a suitable learning process. Hence, the question is how do the policymakers know what activities should be promoted, and how do they learn about the obstacles to the creation of new activities? Rather than assuming that the government has arrived at the right list of market failures and uses development banks to close some well-identified market gaps, this paper suggests that development banks can be in charge of identifying these market failures through their loan-screening and lending activities to guide their operations and provide critical inputs for the design of productive development policies. In fact, they can also identify government failures that stand in the way of development and call for needed public inputs. This intelligence role of development banks is similar to the role that modern theories of financial intermediation assign to banks as institutions with a comparative advantage in producing and processing information. However, while private banks focus on information on private returns, development banks would potentially produce and organize information about social returns.
Keywords: G21; G28; G14; L32; O25; 330; Market imperfections; Industrial policy; Public banks